Neutrino Experiments at the LHC - Kose Umut (EPJ Web of Conferences)
The LHC neutrino experiments, FASER and SND@LHC were approved by the CERN Research Board in 2019 and 2021, respectively, to operate during LHC Run 3. Both experiments began taking physics data in July 2022 and have since recorded approximately 70 fb-1 of data from proton-proton collisions with a center-of-mass energy of 13.6 TeV. These experiments achieved the first direct observation of neutrino interactions at the LHC, using the active electronic components of their detector. Additionally, FASERν, using 2% of its data sample, detected the highest-energy νe and νµ interactions ever observed from an artificial source and made the first measurements of neutrino interaction cross-sections over energy ranges of 560–1740 GeV for νe and 520–1760 GeV for νµ. Additionally, both experiments are actively searching for physics beyond the Standard Model, with FASER already publishing initial results on Dark Photons and Axion-like Particles. In this report, we will discuss the status of the experiments, including the detector concept, performance, and the first physics results from Run 3 data.